A Blended Mobile Learning Model-Context Oriented (BML-CO). - Moreira, Fernando (2014)
The steady increase in the number of mobile devices nowadays, particularly among younger people, leads to the emergence of new paradigms in several areas of activity including education. As an example of a new paradigm in the teaching / learning we could refer the m-learning (mobile learning) that, just as technology, has continued and evolved into the Blended Mobile Learning (BML) model. In this paper we propose a BML context oriented model that relies on the use of open source software for the LMS, mLMS and a tool related to the programming environment. The learning context is a relevant aspect of the proposed model by the technical and economic constraints that BML involves.